2003
DOI: 10.1074/jbc.m301738200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Endothelin Receptors Are Present on Nuclei in Cardiac Ventricular Myocytes

Abstract: Endothelins are thought to act through two specific, plasmalemmal G protein-coupled receptor subtypes, ET A R and ET B R. However, in subfractionated cardiac membranes, ET A R immunoreactivity was detected only in the plasma membrane whereas ET B R immunoreactivity was detected predominantly in membranes of intracellular origin. Confocal microscopy demonstrated the presence of intracellular ET A R and ET B R in ventricular myocytes. ET A R were primarily on plasma membrane (surface membranes and transverse-tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 103 publications
7
116
1
1
Order By: Relevance
“…However, endothelin receptors, as well as several other GPCRs and their effectors, are also present on cardiac nuclear membranes (reviewed in [9][10][11]). Immunocytofluorescence studies have revealed ETA to be primarily in the plasma membrane with some perinuclear staining, whereas ETB localize to the nuclear membrane in ventricular myocytes [12,13]. The presence of GPCR effector molecules at the nuclear envelope or within the nucleus further supports the concept of GPCR signalling at the nuclear membrane [14].…”
Section: Introductionmentioning
confidence: 80%
“…However, endothelin receptors, as well as several other GPCRs and their effectors, are also present on cardiac nuclear membranes (reviewed in [9][10][11]). Immunocytofluorescence studies have revealed ETA to be primarily in the plasma membrane with some perinuclear staining, whereas ETB localize to the nuclear membrane in ventricular myocytes [12,13]. The presence of GPCR effector molecules at the nuclear envelope or within the nucleus further supports the concept of GPCR signalling at the nuclear membrane [14].…”
Section: Introductionmentioning
confidence: 80%
“…Rat cardiac nuclei were isolated as described previously [12]. Briefly, rat hearts were pulverized under liquid nitrogen, resuspended in cold PBS, and homogenized (Polytron, 8000 rpm; 2×10 s, Fraction 1).…”
Section: Isolation Of Nucleimentioning
confidence: 99%
“…SDS PAGE and immunoblotting were performed as previously described [12]. Immunoreactive bands were quantified using a BioRad VersaDoc 4000 imaging system and Quantity One® software (Version 4.5.2 for Mac).…”
Section: Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many receptors that act as signal transducers at the cell membrane are also found in the nuclear envelope (e.g. ET A and ET B receptors [28]) where they might activate a nuclear PIP 2 -PLC-IP 3 cascade. The mechanism for stimulation of nuclear hormone receptors is not entirely clear, although it has been suggested that activated receptors can be internalized from the surface of cells and translocated to the nucleus where they engage signaling pathways.…”
Section: The Abc Of Ip 3 : Where Does It Come From and Where Does It Go?mentioning
confidence: 99%